Heart rate variability of young table tennis players with the use of the Multiball training - Katsikadelis, M.; Pilianidis, T.; Mantzouranis, N.; Fatouros, I.; Agelousis, N. (Biology of Exercise, 2014)
The purpose of this study was to evaluate the heart rate responses of the 2 Multiball Table Tennis interval training protocols during the competitive period on young Table Tennis players. Fourteen (n=14) players, aged 12±2yrs participated in this study. Participants were randomly divided into 2 training duration groups (15s vs. 30s) and were trained under the 2 interval protocols for 6 weeks (3 sessions/w). eart Rate (HR ) data was electronically recorded by using the Polar Team System at the completion of each exercise at the 1st and 5th set in the 1st and 6th week. The Wilcoxon signed-rank test was applied in order to compare the repeated measurements, whereas Spearman`s rank correlation (ñ) analysis was employed to determine whether the testing parameters are significantly related. From the results it is shown that regarding to the HR both training protocols can simulate the match conditions. In both groups participants` the footwork exercises with Forehand and Backhand strokes recorded the higher HR (190-210 b/min). Additionally, significant HR differences were recorded in Group A (z=-2.023, p=0.043) in Footwork Forehand Backhand (FTFB). In conclusion, both Multiball protocols can generally simulate match conditions supporting the weekly training program of young Table Tennis players.